"All There Is": The Reconciliatory Poetics of a Singing Voice. Issue 1 (19th February 2018) - Taylor‐Neu, Robyn
ABSTRACT: In this article, I argue that popular representations of Tanya Tagaq, an Indigenous Canadian musician, shore up a reconciliatory project by mobilizing voice ideologies within densely poetic texts. I trace how commonly held presuppositions and fantasies about Indigeneity in the Canadian multicultural context emerge through and are reinforced by formal aspects of music‐critical discourse. By analyzing how discourse on cultural production figurates reconciliation at various scales, this article contributes to critical understandings of liberal multicultural politics of reconciliation. In so doing, it offers insight into an entanglement of voice, language, and media ideologies in popular journalistic discourse on cultural difference. [ voice, reconciliation, semiotics, Indigeneity, Canada ]